Activity of the museum «The Monuments of Ancient Taraz» (Journal of history, 2018)
In this article the history of the creation of the museum-reserve “The Monuments of Ancient Taraz” was analyzed.The activity of the museum – reserve for the protection of monuments of history and culture of Zhambyl region was determined.Historical reviews were made for the most popular part of the museum, as the city of Taraz, the mausoleum of Aisha Bibi, the mausoleum of Babadzha Khatun, the mausoleum of Karakhan, the mosques Usharal and Abdykadyr.The results of joint work of the specialists of the republican “Kazkaytazhangyrtu” and the museum “Monuments of Ancient Taraz” for restoration, the current situation and the future of the museum were analyzed.